Sistem Pakar Mendiagnosa Penyakit Anemia dengan Menggunakan Metode Teorema Bayes Berbasis Web: (Studi kasus : RSUD.Dr.RM Djoelham Binjai) - Gea, Wisda Wati; Maulita, Yani; Naftali, Juliana (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2021)
Expert systems are a branch of artificial intelligence that studies how to adopt an expert's way of thinking in solving a problem and making a decision to draw conclusions. In this case the expert system is used to diagnose anemia. What is discussed is how to determine the type of disease, how to overcome anemia in the community and designing expert systems using technology. nemia caused by a lack of red blood cells or malfunctioning red blood cells in the body. This causes reduced oxygen flow to the organs of the body. Vitamin B supplements can be used for low vitamin levels. The Bayes method is a method for producing parameter estimates by combining information from samples and other information that has been previously available. Bayes' theorem is used to calculate the probability of an event occurring based on the effects of these observations. From several studies that have been done, it is found a solution to prevent anemia. Anemia can cause weakness and dizziness due to lack of blood, which can lead to complications. The objective is to provide information to assist the general public in diagnosing anemia and getting a preciseand accurate diagnosis.